Professional development in corporate training through learning experiences in the workplace - Çimen, Canan Aratemur. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2009., 2009)
The purpose of this study was to investigate learning experiences of corporate training practitioners in the workplace while acquiring necessary knowledge and skills for their professional development. More specifically, it explored the ways in which practitioners start to work in the profession, the kinds of knowledge and skills needed for professional expertise and the ways of professional development in corporate training. By using a qualitative research method, the research was carried out with thirteen corporate training practitioners within three different private business organizations operating in the banking, retail and telecommunication sectors in İstanbul, Turkey. Semi-structured interviews were conducted with the participants. The data was analyzed through content analysis method. The analysis of data indicated that practitioners generally did not make informed decisions when they started to work in corporate training. Corporate training practitioners defined their roles as consultants and strategic partners within the organization. They were mainly responsible for managing training activities within the organization as a process starting from training needs analysis to measurement and evaluation. To perform these roles and responsibilities, having conceptual knowledge in training and business knowledge together with communication and presentation skills were considered necessary. The findings revealed that professional expertise in corporate training was mostly developed through informal learning experiences in the workplace where formal learning experiences were found as complimentary but insufficient. In the study, there emerged two main categories of informal learning, “learning on their own” and “learning from others”. The informal learning activities under “learning on their own category” included exploration, execution of the job, presenting and self-reflection. The informal learning activities under the “learning from others” category included questioning, consulting and working in projects. The factors influencing practitioners’ informal learning experiences were classified as contextual factors and individual factors. While attitude of managers and colleagues towards practitioners, structure of work, access to learning resources and management attitude towards training were classified under contextual factors, personality characteristics and educational backgrounds of practitioners were classified under individual factors.
Keywords: Adult education teachers -- Training of.